Development, phonotaxis and management of Gryllotalpa africana Palisot de Beauvois (Orthoptera: Gryllotalpidae) on turfgrass - Schoeman, A.S. (University of Pretoria, 2013)
Dissertation (MSc (Entomology))--University of Pretoria, 2005.